Short-term supplementation with dietary fructooligosaccharide and dietary mannitol elevated the absorption of calcium and magnesium in adult rats - Xiao, J.; Sakaguchi, E.; Bai, G. (Czech Journal of Animal Science, 2016)
The effects of dietary fructooligosaccharide (FOS) and dietary mannitol on the absorption of Ca and Mg in a short term feeding trial were studied. Adult Wistar rats were divided into three groups and fed diets containing 0, 8% FOS or 8% mannitol for seven days. Daily intake and feces were monitored for three days to determine the apparent absorption of Ca and Mg. At the last day of the feeding trial, blood sample was collected from cecal vein to assess Ca and Mg levels. The cecum and colon were removed to analyze the parameters. The results showed that both dietary FOS and dietary mannitol significantly increased the apparent absorptions of Ca and Mg. Both dietary FOS and dietary mannitol significantly increased Ca concentration in cecal vein plasma, but did not affect Mg concentration. They significantly decreased Ca concentration and significantly increased soluble Ca concentration in cecal content dry matter (DM). The Mg concentration in colonic content DM was significantly decreased by feeding dietary FOS and dietary mannitol. FOS fermentation in cecum led to low cecal pH and increases in cecal organic acids concentration. Mannitol was fermented in cecum to induce low cecal pH and cecal wall extension. In conclusion, short-term supplementation with dietary FOS and dietary mannitol improved the apparent absorption of Ca and Mg. FOS and mannitol were fermented in cecum to elevate Ca absorption from cecum and to elevate Mg absorption in colon in rats.
Keywords: mannitol; FOS; Ca; Mg; absorption; cecum; rat